Joyful Learning for Enhancing Pedagogical Competence of Islamic Education Teachers in Building Meaningful and Character-Based Learning - Khotimah, Husnul; Priyanto, Eko; Ahmad, Aghniawati (The Indonesian Institute of Science and Technology Research, 2025)
This literature review explores the role of joyful learning in enhancing the pedagogical competence of Islamic education teachers to promote meaningful and character-based learning. Drawing on various scholarly sources, the study identifies joyful learning strategies such as interactive discussions, educational games, storytelling, and multimedia as practical tools for improving instructional planning, classroom management, and student assessment. The review also emphasizes the relevance of Vygotsky’s social constructivist theory, especially scaffolding and social interaction, in supporting joyful and engaging learning experiences. Furthermore, it highlights challenges such as limited professional development and low digital literacy among teachers that may hinder the practical application of joyful learning. The study concludes that joyful learning contributes to pedagogical improvement and the formation of students' moral and spiritual character. Recommendations include the need for systematic training and institutional support to help Islamic education teachers implement joyful learning strategies more effectively in their classrooms.